Questões Estruturais E Medidas De Curto Prazo: Economia Política E Política Econômica No Brasil (1994-2010) - Lourenco, Aline Da Costa [UNIFESP] (2018)
In The Twentieth Century, Brazil Went Through A Period Of Industrialization Through Import Substitution (Isi) That Ended In The Last Years Of The 1980s. Since Then, The Brazilian Economy Is Still Looking For Direction, Always In The Face Of Inflationary Scenarios Or Crises Macroeconomic Variables Such As Those Currently Experienced. In Analyzing The Last Three Decades Of The Brazilian Economy, Two Moments Stood Out For Their Importance And Significance: (I) Economic Stabilization With The Implementation Of The Real Plan In 1994 And (Ii) A Distinct Dynamic From 2006 And More Directly In 2008 , With The Global Crisis. In This Way, The Objective Of This Work Is To Determine And Analyze The Determinants That Led To The Decision Making In The Macroeconomic Policies In These Two Periods. The Initial Hypothesis Of Work Is About The Possibility That The Adoption Of The Economic Measures In These Two Periods Initially Had A Character More Affective To The Conditions Of Short Term. It Is Intended To Discuss The Form An